2001
DOI: 10.1002/jcp.10045
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Caco‐2 cell proliferation by all‐trans retinoic acid: Role of insulin‐like growth factor binding protein‐6

Abstract: The present study examined the effects of all-trans retinoic acid (tRA) on proliferation and expression of the IGF system in Caco-2 human colon adenocarcinoma cells. tRA inhibited Caco-2 cell proliferation in a dose-dependent manner, with a 40 +/- 2% decrease in cell number observed 48 h after the addition of 1 microM tRA. Ligand blot analysis of IGFBPs in conditioned media revealed that Caco-2 cells produced three IGFBPs of M(r): 34,000 (IGFBP-2), 24,000 (IGFBP-4), and 32,000 (IGFBP-6). The concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 50 publications
3
34
0
Order By: Relevance
“…Using an anti-IGFBP-6 antibody, an apporximately 32-kDa band was seen only in the CM of fascia ( Figure 4). The size of the band was consistent with that previously described for IGFBP-6 (Kim et al, 2002). None of the desmoid CM samples demonstrated any detectable bands.…”
Section: Confirmation At the Protein Levelsupporting
confidence: 89%
“…Using an anti-IGFBP-6 antibody, an apporximately 32-kDa band was seen only in the CM of fascia ( Figure 4). The size of the band was consistent with that previously described for IGFBP-6 (Kim et al, 2002). None of the desmoid CM samples demonstrated any detectable bands.…”
Section: Confirmation At the Protein Levelsupporting
confidence: 89%
“…IGFBP-6 is expressed in many cell types, such as fibroblasts, myoblasts, smooth muscle cells, keratinocytes, and osteoblasts (Yan et al, 2001;Strohbach et al, 2008). Because of its binding preference, IGFBP-6 might regulate IGF-II-induced cell proliferation, differentiation, and survival (Bach et al, 1994;Dake et al, 2002;Kim et al, 2002;Gallicchio et al, 2003;Fu et al, 2007). Generally, IGFBPs play an IGF-dependent role in high affinity IGF binding.…”
Section: Introductionmentioning
confidence: 99%
“…Caco-2 cells were maintained and subcultured as previously described [9]. To determine the growth characteristics of individual clones, cells were plated in 24 well plates with DMEM/F12 containing 10% FBS.…”
Section: Cell Culturementioning
confidence: 99%
“…Multiple isoforms of pro IGF-II (pIGF-II) resulting from alternative processing and glycosylation have been identified [7,8]. The human colon adenocarcinoma cell line, Caco-2, utilized in the present study, secretes both mature 7500 M r and higher M r forms of IGF-II (pIGF-II) [9,10], and IGF-II acts as an autocrine growth regulator of these cells [11,12]. We have previously observed that compounds which inhibit cancer cell proliferation also inhibit the production of mIGF-II and pIGF-II [10].…”
Section: Introductionmentioning
confidence: 99%